External shocks and populism - Eugenio Levi; Steven Stillman (EconPol Forum, 2024)
In this report, we examine the impact that two large external shocks, one related to structural reform and another to immigration policy, had on the initial development and long-term success of New Zealand First (NZF), one of the oldest populist parties in the OECD. Using survey data together with localized geographic identifiers, we investigate a rich set of mechanisms underlying the impact of the shocks, namely political beliefs and preferences, individual and community characteristics. We find that both shocks had an important role in the initial development of NZF. Economic, cultural, and political explanations of the development of political populism in NZ are found to be highly intertwined. The shocks caused an increase in mistrust towards the mainstream parties and in feelings that a strong leader is needed, while "losers" of structural reforms and of immigration flows are not found to be more inclined to vote for NZF. Furthermore, the impact of these shocks was found to be concentrated in rural or less cosmopolitan geographical areas. The impact of these shocks on populist voting persisted in the medium term and still had an influence after 20 years. It also led to a rightward shift in political preferences.
Keywords: 330